2007
DOI: 10.1128/mcb.02043-06
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Roles of Vertebrate Fbh1 and Blm DNA Helicases in Avoidance of Crossovers during Recombination Initiated by Replication Fork Collapse

Abstract: Fbh1 (F-box DNA helicase 1) orthologues are conserved from Schizosaccharomyces pombe to chickens and humans. Here, we report the disruption of the FBH1 gene in DT40 cells. Although the yeast fbh1 mutant shows an increase in sensitivity to DNA damaging agents, FBH1؊/؊ DT40 clones show no prominent sensitivity, suggesting that the loss of FBH1 might be compensated by other genes. However, FBH1؊/؊ cells exhibit increases in both sister chromatid exchange and the formation of radial structures between homologous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
44
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 44 publications
6
44
0
Order By: Relevance
“…1D and Table S1). The latter type of break is likely caused by HR-dependent repair between the broken and the intact sister chromatids, followed by defective resolution of recombination intermediates (33). Taking roles of SLX1 (21,26), XPF-ERCC1 (34)(35)(36), and MUS81-EME1 (37,38) in HR into account, our findings thus support the hypothesis that SLX4 deficiency causes impaired resolution of HR intermediates, possibly through the disruption of functional SLX4 complex, including these structure-specific endonucleases.…”
Section: Slx4 Is Essential For Cell Proliferationsupporting
confidence: 75%
“…1D and Table S1). The latter type of break is likely caused by HR-dependent repair between the broken and the intact sister chromatids, followed by defective resolution of recombination intermediates (33). Taking roles of SLX1 (21,26), XPF-ERCC1 (34)(35)(36), and MUS81-EME1 (37,38) in HR into account, our findings thus support the hypothesis that SLX4 deficiency causes impaired resolution of HR intermediates, possibly through the disruption of functional SLX4 complex, including these structure-specific endonucleases.…”
Section: Slx4 Is Essential For Cell Proliferationsupporting
confidence: 75%
“…The suppressor gene was identified as the F-box helicase Fbh1 (Osman et al 2005), which has also been found in vertebrates, but not in budding yeast ( J. Kohzaki et al 2007). …”
Section: H Omologous Recombination (Hr) Is An Impor-mentioning
confidence: 99%
“…To date, no apparent Srs2 ortholog has been identified in other eukaryotes, although the recently identified Fbh1 helicase shows some structural similarity to the Srs2 helicase family and studies in Schizosaccharomyces pombe suggest that Fbh1 plays a role in processing HR intermediates (Osman et al 2005;Morishita et al 2005). However, Fbh1-deficient DT40 cells show no prominent sensitivity to DNA damaging agents, and exhibit only a mild SCE phenotype (Kohzaki et al 2007). This raises the question as to whether attenuation of HR by disruption of the Rad51 presynaptic filament represents a significant mechanism for HR regulation in higher eukaryotes.…”
mentioning
confidence: 99%